The naturalization of male chauvinism in adolescents through fiction series - Bandrés-Goldáraz, Elena (2022)
Since Spanish Government implemented the first measures to advise women on their labour and social rights and also to assist victims of gender violence, in 1984, practically all efforts drawn up have It includes raising the awareness of the media to eradicate the stereotypes with which the image of women is conformed.From the interaction of High School students with their favourite TV series, such as La que se avecina, The Big Bang Theory, Big Brother or MyHyV, among the most watched, three things can be seen. Results. That teenagers are not bothered by the stereotypes that undermine gender equality present in these TV series; that they have incorporated into their daily lives the funny phrases and catch phrases that are repeated in the series by characters that can be described as sexist, and that these girls and boys suffer in their immediate environment a macho ideology in line with the scenes that their favourite characters have often starred their favourite characters. So, it can be said that this type of fiction is naturalizing the presence of sexist violence in their lives, both symbolic and real.